Intra and Inter-Individual Variability in the Chaotic Component and Functional Connectivity of the Eeg Signal in Basal Eyes Closed Condition - Diaz-Munoz, H (Elsevier B.V., 2019)
Individuality has to do with our differences and similitudes, our phenotype and genotype characteristics that make us unique in some ways, and common in others. In this study we applied linear and non-linear quantitative description of the EEG signal of 8 subjects in closed eyes, basal conditions, three times at a day (at 10:00, 13:00, and 16:00 hrs. UTC -04:00 Santiago), to provide evidence that allows us to narrow the boundaries of intra and inter-individual differences in the behavior of the oscillatory electrical signal of the brain. We applied two versions of Hurst exponent estimator of persistence/anti-persistence of the brain signal, and a Spearman R inter-correlation analysis between pairs of EEG channels to quantify and allocate the magnitude of highly correlated pairs of electrodes as an indicator of enhanced brain synchrony. Results showed differences and patterns in laterality/symmetry associated with magnitude, self-organized long-memory processes; and brain synchrony. © 2020 The Authors. Published by Elsevier B.V.